Development and Research of a Theoretical Model of the Magnetic Tunnel Junction - Oleg Polyakov; Vladimir Amelichev; Dmitry Zhukov; Dmitry Vasilyev; Sergey Kasatkin; Peter Polyakov; Dmitry Kostyuk (Sensors, 2021)
Spin-dependent tunneling structures are widely used in many spintronic devices and sensors. This paper describes the magnetic tunnel junction (MTJ) characteristics caused by the inhomogeneous magnetic field of ferromagnetic layers. The extremely oblate magnetic ellipsoids have been used to mimic these layers. The strong effect of an inhomogeneous magnetic field on the magnetoresistive layers’ interaction was demonstrated. The magnetostatic coupling coefficient is also calculated.